Transparent, Ultra-Stretching, Tough, Adhesive Carboxyethyl Chitin/Polyacrylamide Hydrogel Toward High-Performance Soft Electronics - Zhang, Jipeng; Hu, Yang; Zhang, Lina; Zhou, Jinping; Lu, Ang (Nano-Micro Letters, 2022)
To date, hydrogels have gained increasing attentions as a flexible conductive material in fabricating soft electronics. However, it remains a big challenge to integrate multiple functions into one gel that can be used widely under various conditions. Herein, a kind of multifunctional hydrogel with a combination of desirable characteristics, including remarkable transparency, high conductivity, ultra-stretchability, toughness, good fatigue resistance, and strong adhesive ability is presented, which was facilely fabricated through multiple noncovalent crosslinking strategy. The resultant versatile sensors are able to detect both weak and large deformations, which owns a low detection limit of 0.1% strain, high stretchability up to 1586%, ultrahigh sensitivity with a gauge factor up to 18.54, as well as wide pressure sensing range (0–600 kPa). Meanwhile, the fabrication of conductive hydrogel-based sensors is demonstrated for various soft electronic devices, including a flexible human–machine interactive system, the soft tactile switch, an integrated electronic skin for unprecedented nonplanar visualized pressure sensing, and the stretchable triboelectric nanogenerators with excellent biomechanical energy harvesting ability. This work opens up a simple route for multifunctional hydrogel and promises the practical application of soft and self-powered wearable electronics in various complex scenes. Highlights: 1 Hydrogel demonstrates superior merits of strain (1586%), self-adhesion (113 kPa for pigskin), high conductivity and transparency (92%). 2 The wearable sensors with a gauge factor up to 18.54, wide pressure sensing range (0–600 kPa) enable the detecting, quantifying, and monitoring of human activities. 3 The hydrogels were developed as electronic skin, high output stretchable CTA-TENGs and explored using as wearable keyboards for human-machine interaction.